Modelling of solid state impulse generator - Said, Zainudin (2000)
This paper presents the application of solid state device used in the impulse generator. Through the advancement of solid state technology, these devices are widely used in high voltage testing. The principle of high voltage Marx Generator is employed by means modeling high scale into low scale circuit. MOSFET is used to replace the sphere gap as switching device. The uses of this device is very important in order to control charging and discharging process beside setting the square wave supply. Pspice simulation is the theoretical comparison to the experimentation that had been conducted in the laboratory.